Rhinomaxillary mucormycosis in an immunocompetent individual: Importance of early diagnosis - Sunira Chandra; Siva Prasad Reddy Enja; Nitin Nigam; Suzanne Nethan (Wolters Kluwer Medknow Publications, 2014)
Rhinomaxillary mucormycosis presents with a characteristic destruction and necrosis most commonly affecting immunocompromised patients, especially diabetics. The present reported case was extremely unusual that the characteristic clinical feature of ulceration or necrosis was absent and the patient was apparently healthy (immunocompetent) with mere findings of generalized periodontal pockets, mobility of maxillary teeth, and a diffuse mild swelling in the anterior region of the hard palate on initial (clinical and radiographic) examination. This emphasized the need to include this fatal opportunistic infection in the differential diagnosis of maxillary swellings in otherwise healthy patients showing minimal clinical signs which could camouflage its presence.